SISTEM INFORMASI GEOGRAFIS BUDAYA DAN EKOWISATA MENGGUNAKAN ALGORITMA DIJKSTRA DENGAN GOOGLE MAPS API DAN JAVA SERVER PAGE (DISPORABUDPAR MAJALENGKA) - Oo Satia; Harun Sujadi (PROCEEDING STIMA)
One of the important infrastructure considered by the government to realize the ideals of developed countries, namely Indonesia adequate road infrastructure as traffic (Traffic) supporting the economy. Where the government did it all so that tourists who come both from outside and within the country can enjoy a smooth journey they planned to do to the destination. In Majalengka many sites of cultural or legal or who already has received permission from the local government. With this method Djikstra algorithm, road users or tourists who will visit tourist attraction will be faster. Djikstra algorithm is a greedy algorithm where the algorithm in use to look for problems shortest route between a source node and the destination node for a directed graph based on weight on the side that is not worth the negative. This algorithm works by visiting the nodes there, starting from the source node.Keywords: GIS, Google Maps API, Algorithm Djikstra, JSP